Compartilhamento de torque do tríceps sural e do tibial anterior na flexão plantar isométrica em indivíduos com doença de Parkinson - Peixoto, Bruna Luzia da Silva (2017)
Parkinson's disease (PD) is a progressive neurodegenerative disease characterized by resting tremor, bradykinesia, rigidity and postural instability. Musculoskeletal changes are observed, such as muscle weakness and shortening, which directly interfere with functional performance. The aim of this study was to quantify the distribution of isometric ankle torque between the components muscle triceps surae (TS): gastrocnemius medialis (GM), lateralis (GL) and soleus; and the tibialis anterior (TA) as the main antagonist. Two groups, elderly with PD and apparently healthy elderly, were instructed to perform isometric plantar flexion steps at 10, 40 and 60% of maximum torque (MVC) in an isokinetic dynamometer. Signals of torque and electromyography (EMG) were acquired synchronously. An EMG-Driven muscle mechanics model was applied to estimate the individual torque generated by each of the four muscles. The mean square error between estimated and measured total torque was calculated. In the PD group, the plantar flexion torque sharing followed an increasing order: 10% step: GM = 17.9%, GL = 19.7% and soleus = 62.4%; 40% step: GM = 21%, GL = 20.6%, soleus = 58.4%; and step 60% GL = 18%, GM = 24.6%, soleus = 56.2%. The TA showed a decreasing participation: 7.8%, 4.7% and 3.9% for the 10, 40 and 60% steps, respectively. Significant differences between the GL (PD> CG) and GM (PD<CG) contributions to the plantar flexor torque were observed. Increased TA coconcentration was observed for PD. The %RMS torque error was similar between the groups and distinct among the contraction intensities. It was concluded that there was a significant difference in the ankle plantar flexor torque sharing pattern between PD and apparently healthy elderly.